Engineering computations and modeling in MATLAB/Simulink - Yakimenko, Oleg A. (American Institute of Aeronautics and Astronautics, Inc., 2020)
"Engineering Computations and Modeling in MATLAB/Simulink, Second edition provides a broad overview of The MathWorks' MATLAB/Simulink/GUIDE/App Designer development and modeling environment. This textbook shows how to use these software tools effectively in a variety of engineering applications, including modeling real-world dynamic systems. This book is used as a textbook by undergraduate and graduate students taking both introductory and advanced courses in applied programming, and also as a reference for working professionals using MATLAB/Simulink"-- Provided by publisher.
Keywords: MATLAB.; SIMULINK.; MATLAB; SIMULINK; Engineering mathematics -- Data processing.; Computer programming.; elektronické knihy; electronic books